Valuing consumer preferences and motivations for plant-based beverages: A CUB model analysis - Giulia Mastromonaco; Stefano Massaglia; Danielle Borra; Francesco Sottile; Cristiana Peano; Mingze Rui; Oriana Mosca; Valentina Maria Merlino (Future Foods)
Food consumption trends have evolved significantly in recent years due to increased attention to environmental sustainability and the search for nutritionally balanced, health-beneficial food. In this context, plant-based beverages (PBBs) represent a rapidly growing segment. This study analyses the PBBs preferences and motivations of consumption, studying how socio-demographic characteristics influence purchase drivers and identifying the role of certification-related eating styles and habits in the importance attributed to PBBs characteristics. An online questionnaire was conducted in the South-East of Italy with a sample of 233 respondents. A methodology utilising a Combination of Uniform and Shifted Binomial random variables, the CUB model, was employed to assess consumers' perceptions across two key dimensions: feeling and uncertainty. Results suggest that the two most important PBBs attributes considered in the decision-making process were taste and expiration date; the main reasons for PBBs consumption were the presence of vitamins and minerals and beneficial health ingredients. Moreover, considering socio-demographic characteristics and the consumption habits as covariates, different profiles of consumers of this product emerged. This research fill gaps in the literature on consumer characterisation of PBBs and offers a broader perspective, including the examination of attributes where consumers are uncertain about the level of importance they attach.